The ride of her life [large type] : the true story of a woman, her horse, and their last-chance journey across America - Letts, Elizabeth (Random House Large Print, 2021)
The #1 New York Times best-selling author of "The perfect horse" and "The eighty-dollar champion" presents the triumphant true story of 63-year-old Maine farmer Annie Wilkins who, in 1954, rode her horse across America, fulfilling her dying wish to see the Pacific Ocean.